Adsorption and self-assembly of porphyrins on ultrathin CoO films on Ir(100) - Xiang, Feifei; Schmitt, Tobias; Raschmann, Marco; Schneider, M. Alexander (Beilstein Journal of Nanotechnology, 2020)
Porphyrins represent a versatile class of molecules, the adsorption behavior of which on solid surfaces is of fundamental interest due to a variety of potential applications. We investigate here the molecule-molecule and molecule-substrate interaction of Co-5,15-diphenylporphyrin (Co-DPP) and 2H-tetrakis(p-cyanophenyl)porphyrin (2H-TCNP) on one bilayer (1BL) and two bilayer (2BL) thick cobalt oxide films on Ir(100) by scanning tunneling microscopy (STM) and density functional theory (DFT). The two substrates differ greatly with respect to their structural and potential-energy landscape corrugation with immediate consequences for adsorption and self-assembly of the molecules studied. On both films, an effective electronic decoupling from the metal substrate is achieved. However, on the 1BL film, Co-DPP molecules are sufficiently mobile at 300 K and coalesce to self-assembled molecular islands when cooled to 80 K despite their rather weak intermolecular interaction. In contrast, on the 2BL film, due to the rather flat potential landscape, molecular rotation is thermally activated, which effectively prevents self-assembly. The situation is different for 2H-TCNPP, which, due to the additional functional anchoring groups, does not self-assemble on the 1BL film but forms self-assembled compact islands on the 2BL film. The findings demonstrate the guiding effect of the cobalt oxide films of different thickness and the effect of functional surface anchoring.
CRIS-Team WoS Importer:2020-10-23

Adsorption Behavior of a Cyano-Functionalized Porphyrin on Cu(111) and Ag(111): From Molecular Wires to Ordered Supramolecular Two-Dimensional Aggregates - Lepper, Michael; Schmitt, Tobias; Gurrath, Martin; Raschmann, Marco; Zhang, Liang; Stark, Michael Werner; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Schneider, M. Alexander; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physical Chemistry C, 2017)
We investigate the impact of peripheral cyano functionalization of the previously well-studied 2H-tetraphenylporphyrin (2HTPP) by scanning tunneling microscopy (STM) and density functional theory (DFT). The adsorption behavior of 2H-tetralds(p-cyano)-phenylporphyrin (2HTCNPP) is studied at room temperature and at 80 K on Cu(111) and Ag(111). Interestingly, the cyano-functionalized porphyrins tend to form isolated ID chains on Cu(111), in particular after mild annealing at 350 K. The individual 2HTCNPPs as well as the formed chains are oriented along the main crystallographic directions of the Cu(111) substrate due to a strongly attractive and site-specific interaction between the iminic nitrogens of the 2HTCNPP and Cu substrate atoms. The linking within the 1D molecular chains is realized by Cu adatoms as evidenced by comparison of STM and DFT. In contrast, on Ag(111) the molecules assemble into 2D supramolecular layers with long-range order and a square unit cell, stabilized by molecule-molecule interactions. The orientation of the molecules with respect to the unit cell lattice vectors leads to organizational chirality. By codeposition of cobalt, the porphyrin molecules are metalated at room temperature. We did not observe any evidence for metal-organic network formation on Ag(111), even after varying the deposition parameters or the order of metal and porphyrin deposition. Our study shows that cyano functionalization of porphyrins can give rise to novel and unique self-assembled structures like 1D molecular chains without any cross-connections via adatom linking.

Coverage-Dependent Anchoring of 4,4 '-Biphenyl Dicarboxylic Acid to CoO(111) Thin Films - Mohr, Susanne; Schmitt, Tobias; Döpper, Tibor; Xiang, Feifei; Schwarz, Matthias; Görling, Andreas; Schneider, M. Alexander; Libuda, Jörg (Langmuir, 2017)
We investigated the adsorption behavior of 4,4'-biphenhyl dicarboxylic acid (BDA) on well-ordered CoO(111) films grown on Ir(100) as a function of coverage and temperature using time-resolved and temperature programmed infrared reflection absorption spectroscopy (TR-IRAS, TP-IRAS) in combination with density functional theory (DFT) and scanning tunneling microscopy (STM) under ultrahigh vacuum (UHV) conditions. To compare the binding behavior of BDA as a function of the oxide film thickness, three different CoO(111) film thicknesses were explored: films of about 20 bilayers (BLs) (approximately 5 nm), 2 BLs, and 1 BL. The two carboxylic acid groups of BDA offer two potential anchoring points to the oxide surface. At 150 K, intact BDA adsorbs on 20 BL thick oxide films in planar geometry with the phenyl rings aligned parallel to the surface. With decreasing oxide film thickness, we observe an increasing tendency for deprotonation and the formation of flat-lying BDA molecules anchored as dicarboxylates. After saturation of the first monolayer, intact BDA multilayers grow with molecules aligned parallel to the surface. The BDA multilayer desorbs at around 360 K. Completely different growth behavior is observed if BDA is deposited above the multilayer desorption temperature. Initially, doubly deprotonated dicarboxylates are formed by adopting a flat-lying,orientation. With increasing exposure, however, the adsorbate layer transforms into upright standing monocarboxylates. A sharp OH stretching band (3584 cm(-1)) and a blue-shifted CO stretching band (1759 cm(-1)) indicate weakly interacting apical carboxylic acid groups at the vacuum interface. The anchored monocarboxylate phase slowly desorbs in a temperature range of up to 470 K. At higher temperature, a flat-lying doubly deprotonated BDA is formed, which desorbs and decomposes in a temperature range of up to 600 K.

Evidence for On-Site Carboxylation in the Self-Assembly of 4,4′-Biphenyl Dicarboxylic Acid on Cu(111) - Schmitt, Tobias; Hammer, Lutz; Schneider, M. Alexander (Journal of Physical Chemistry C, 2016)
Molecular self-assembly at surfaces is controlled by a complex balance between molecule-substrate and intermolecular interactions. The occurrence of chemical reactions at the surface will alter the governing hierarchy of interaction energies substantially. An important aspect in this respect is whether the chemical reaction happens independently from the self-assembly process, such that reacted species form ordered structures, or whether the reaction is an integral part of the self-assembly process and is triggered during the formation of ordered structures. We report on a low-temperature scanning tunneling microscopy study of ordered phases of 4,4′-biphenyl dicarboxylic acid on Cu(111) at submonolayer coverage in ultrahigh vacuum. For this system the thermally activated carboxylation reaction influences the formation of molecular structures significantly. We find evidence that near room temperature the deprotonation of a molecule is triggered by the specific configuration of neighboring molecules allowing the formation of a complex, well-ordered structure combining intact and deprotonated molecules.
Created from Fastlane, Scopus look-up

Incommensurate Moire overlayer with strong local binding: CoO(111) bilayer on Ir(100) - Tröppner, Carsten; Schmitt, Tobias; Reuschel, Martina; Hammer, Lutz; Schneider, M. Alexander; Mittendorfer, Florian; Redinger, Josef; Poudlucky, Raimund; Weinert, Michael (Physical Review B, 2012)
Incommensurate relaxed overlayer Moire structures are often interpreted as systems with weak lateral variations of the binding potential and thus no structural modulations in the overlayer material. We discuss here the example of a CoO(111) bilayer on Ir(100), which is a relaxed overlayer with strong structural response to the lateral modulation of interface properties but nevertheless is incommensurate. By means of density functional theory (DFT) calculations, we quantitatively reproduce all the structural parameters of the CoO(111) bilayer on Ir(100) as proposed by a recent low-energy electron diffraction analysis [Ebensperger et al., Phys. Rev. B 81, 235405 (2010)]. The calculations predict energetic degeneracies with respect to registry shifts of the CoO(111) film along [01 (1) over bar]. Large-scale, low-temperature scanning tunneling microscopy topographies reveal that the true structure of the film is incommensurate in this direction, exhibiting a one-dimensional Moire pattern with a period of about 9.4 a(Ir). From DFT calculations for limiting (periodic) models, we can sample the potential landscape of the cobalt and oxygen atoms in the Moire structure across the Ir(100) unit cell. We find that despite the non-commensurability of the film, the binding to the substrate is site specific with strong attraction and repulsion points for both cobalt and oxygen atoms, leading to severe local distortions in the film. The lateral modulation of the structural elements within the oxide film can be understood as a combination of the lateral variation in the Co-Ir binding potential and additional O-Ir binding. DOI: 10.1103/PhysRevB.86.235407

"Inverted'' porphyrins: a distorted adsorption geometry of free-base porphyrins on Cu(111) - Lepper, Michael; Köbl, Julia; Schmitt, Tobias; Gurrath, Martin; De Siervo, Abner; Schneider, M. Alexander; Steinrück, Hans-Peter; Meyer, Bernd; Marbach, Hubertus; Hieringer, Wolfgang (Chemical Communications, 2017)
Based on density functional theory calculations combined with experimental results, we report and discuss an extremely distorted, "inverted'' adsorption geometry of free-base tetraphenylporphyrin on Cu(111). The current findings yield new insights into a wellstudied system, shedding light on the peculiar molecule-substrate interaction and the resulting intramolecular conformation.